Intermediate products of purine metabolism in an experimental model of pancreatic necrosis: Purine bases as predictors of pancreatic necrosis - Abramov, Grigoriy; Pozdnyakova, Yelena; Tankibaeva, Neila; Shakeev, Kairat; Tusupbekova, Maida; Shestakov, Dmitriy (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Determine the level of purines in the blood plasma of experimental animals at three stages of induced pancreatic necrosis. Find out the potential of purines as predictors of the severity of pancreatitis.Methods: The experiment was carried out on white outbred rabbits. The pancreatic necrosis was modeled by introducing self-bile into the pancreatic parenchyma. The pancreas of rabbits, after isolation, was subjected to microscopic description. Blood was also taken from rabbits to determine the plasma levels of adenine, guanine, hypoxanthine, xanthine, and uric acid.Results: 12 hours after the administration of self-bile, the level of xanthine significantly increases and the concentration of uric acid in the blood plasma increases by 3 times. 24 hours after the introduction of self-bile, there is a slight decrease in the level of adenine, xanthine and uric acid, and the indicators of purine metabolism remain elevated. 48 hours after the introduction of self-bile, the levels of guanine, hypoxanthine and xanthine are reduced.Conclusions: The concentration indices of absolute and relative intermediate products of purine metabolism were increased at the initial stage of pancreatic necrosis. The activity of enzymes and metabolites of purine metabolism involved in the formation of reactive oxygen species and free radicals increased. The hypothesis that intermediate products of purine metabolism can be predictors of pancreatic necrosis was confirmed.